Real options valuation of franchise territorial exclusivity - Lukito Adi Nugroho; David McMillan (Cogent Business & Management, 2017)
With the maturity of the franchise system, franchisors have to look for new markets to capitalize constantly. This continuing expansion comes at the expense of the existing franchise establishments, as it could lead to territorial encroachment. One possible solution to mitigate this problem is by offering territorial exclusivity rights (TER) of new potential location to the existing franchisee. Yet, pricing the value of TER is not simple due to contingent claim nature of this rights. Hence, the goal of this paper is to model the TER using real options approach, a financial options valuation method that applies in real business. The real options will be built using Datar–Mathews method and then simulated using hypothetical case data. Results and implications are also discussed.
Keywords: 650